A Review – Role Of Sandhaniya Mahakashaya In The Management Of Wound Healing - Sivan, Archana; Khandelwal, Priyanka; Singh, Chandan; Purvia, Rajendra prasad; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2021)
Wound, known by the term ‘Vrana’ in Ayurveda refers to the Injury of Skin. More specifically explained as the damage caused to the Epidermis of Skin by any kind of Injury. Nowadays, the most challenging clinical problem faced by the clinicians is the Healing of Wounds. Therefore, one has to adopt a correct and efficient clinical treatment protocol. Ayurveda, the ancient traditional system of medicine is with a rich source of knowledge and is known as Ethnopharmacological and Folklore based system. Charaka Samhita, one of the famous treatises of this traditional medicine, is with a rich heritage of knowledge. In Sutra Sthana, 4th chapter “Shad Virechana Shatashriteeya”of Charaka Samhita, Acharya has explained about 50 Mahakashaya or Dashemani. These are groups containing 10 herbs each, exhibiting one common Pharmacological action. One such group is, the Sandhaniya Mahakashaya, called Unifying medicine [1]. It includes: - Madhuyashthi[Glycyrrhiza glabra Linn.], Guduchi [Tinospora cordifolia Miers.], Prishniparni[Uraria picta Desv.], Patha[Cissampelos pareria Linn.], Lajjalu[Mimosa pudica Linn.], Mocharasa[Bombax ceiba Burm.f.], Dhataki[Woodfordia fruticosa Kurz.], Lodhra[Sympolcos racemosa Roxb.], Priyangu[Callicarpa macrophylla vahl.], Katphala[Myrica esculenta Buch-Ham.]. It is well-known fact that, certain plants can repair the wound in their natural way. Therefore this traditional system of medicine helps in finding that specifically apt herbal drugs, which can help in Regeneration and Growth promotion of the damaged body tissues. So in this article, each drugs of Sandhaniya Mahakashaya are explained concerning its ability to manage the wound.